Islamic Religious Education Teacher Learning Strategies in the Independent Curriculum to Face The Challenges of Globalisation - Rizal, Syamsul; Qudratullah, Ihsan (Ta'dib: Jurnal Pendidikan Islam dan Isu-Isu Sosial, 2024)
Abstract The purpose of this study is to find out the Islamic Religious Education Teacher's strategy in the Merdeka Curriculum to face the challenges of globalisation in Class VII of SMP Negeri 2 Batukliang, to find out the school teacher's efforts to improve the Islamic Religious Education learning strategy in the Merdeka Curriculum to face the challenges of globalisation in Class VII of SMP Negeri 2 Batukliang. The research method used is a qualitative research method with a type of descriptive research (field Reseach) field research. The key informants are the principal, vice principal, teacher, homeroom teacher VII of SMPN 2 Batukliang. Techniques used in data collection, researchers use interview techniques, observation, documentation. While data analysis techniques using qualitative descriptive techniques. The results of research on Islamic Religious Education (PAI) learning strategies in the Merdeka Curriculum at SMPN 2 Batukliang reveal the learning strategies implemented by Islamic Religious Education (PAI) teachers in class VII of SMPN 2 Batukliang in order to face the challenges of globalisation, in accordance with the Merdeka Curriculum. The four main strategies found are: cooperative, collaborative, contextual, and project-based learning. Cooperative learning invites students to work together in groups, developing social and communication skills that are essential in the era of globalisation. Other efforts made by teachers include the development of contextualised materials based on Islamic values, linking them to global issues such as the impact of social media and popular culture. Collaboration between students is also enhanced through the application of co-operative and project-based strategies, where students share roles in small groups. In addition, teachers also reinforce the use of project-based learning as well as problem-based learning (PBL) methods to motivate students to develop critical thinking, problem-solving and collaboration skills. In conclusion, these adaptive strategies not only develop students' understanding of religious values but also prepare them for the challenges of globalisation with strong skills and character.